Financial Sector Competition, Service Trade, and Growth - Joseph F. Francois; Felix Eschenbach (Tinbergen Institute, 2002)
We explore dynamic linkages between financial/banking sector openness, financial sector competition, and growth. We first develop an analytical model, highlighting links between long-run economic performance and services trade, through scale economies and market and cost structures in the financial services sector. This is folIowed by an econometric exercise based on data for 130 countries for the 1990s. Our resu1ts point to a strong positive relationship between financia1 sector competition/performance and financia1 sector openness (meaning foreign bank access to domestic markets), and between growth and financial sector competition/performance. They also point to the presence of sca1e economies in the sector.
Keywords: F40; F13; F43; G15; 330; financial services trade; financial sector openness; service trade and imperfect competition; trade in services and growth; banking and growth.; Bank; Wettbewerb; Finanzdienstleistung; Dienstleistungshandel; Wirtschaftswachstum; Unvollkommener Wettbewerb; Welt